2022
DOI: 10.1101/2022.08.01.502293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compensatory mutations reducing the fitness cost of plasmid carriage occur in plant rhizosphere communities

Abstract: Plasmids drive bacterial evolutionary innovation by transferring ecologically important functions between lineages, but acquiring a plasmid often comes at a fitness cost to the host cell. Compensatory mutations, which ameliorate the cost of plasmid carriage, promote plasmid maintenance in simplified laboratory media across diverse plasmid-host associations. Whether such compensatory evolution can occur in more complex communities inhabiting natural environmental niches where evolutionary paths may be more cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Mutations in TrfA44 can inhibit its interaction with DnaB, resulting in mitigation of the fitness cost (Yano et al, 2016). Several studies have shown that compensatory mutations can ameliorate the cost of carriage of the plasmid pQBR103 in Pseudomonas spp., not only under laboratory conditions (Harrison et al, 2015(Harrison et al, , 2016, but also in the rhizosphere (Bird et al, 2023). Mutations in the GacA/GacS system encoded on the host chromosome can reduce the fitness cost of plasmid carriage (Harrison et al, 2015).…”
Section: Compensatory Mutations Can Resolve the 'Plasmid Paradox'mentioning
confidence: 99%
“…Mutations in TrfA44 can inhibit its interaction with DnaB, resulting in mitigation of the fitness cost (Yano et al, 2016). Several studies have shown that compensatory mutations can ameliorate the cost of carriage of the plasmid pQBR103 in Pseudomonas spp., not only under laboratory conditions (Harrison et al, 2015(Harrison et al, , 2016, but also in the rhizosphere (Bird et al, 2023). Mutations in the GacA/GacS system encoded on the host chromosome can reduce the fitness cost of plasmid carriage (Harrison et al, 2015).…”
Section: Compensatory Mutations Can Resolve the 'Plasmid Paradox'mentioning
confidence: 99%